Platinum group metals for nuclear medicine, a luxurious dream or the future of imaging and therapy: a review - Racz, Daniel G.; Chaple, Ivis F. (Frontiers in Nuclear Medicine, 2025)
Platinum group metals (PGMs) consist of six transition metals: platinum (Pt), palladium (Pd), rhodium (Rh), osmium (Os), iridium (Ir), and ruthenium (Ru). PGMs have been used notably in industrial, electronic, and medical applications. For example, Ir-192 is often utilized in industry to detect structural defects in metal and assess pipeline integrity. Pd-104 is irradiated to produce Pd-103 seeds, used for prostate cancer treatment. Other isotopes of elements in this group can be sourced to facilitate critical applications, discussed in this review. Due to their unique chemical and nuclear properties, these metals may be promising candidates for various nuclear medicine applications, including diagnostic imaging via Positron Emission Tomography (PET), Single Photon Emission Computed Tomography (SPECT) and Targeted Radionuclide Therapy (TRT). This review will explore PGMs in nuclear medicine, focusing on their production routes, nuclear characteristics, and suitability for past and future development of radiopharmaceuticals. We will highlight methods for radiochemical separation and purification of each radionuclide, discussing potential challenges and emphasizing the need for further research to ensure sustainability. As the demand for advanced nuclear medicine techniques continues to grow, PGMs may play a significant role in addressing current challenges in the field. We will discuss several radionuclides of interest to nuclear medicine including 191Pt, 193mPt, 195mPt, 103Pd, 109Pd, 103mRh, 105Rh, 191Os, 192Ir, 97Ru, and 103Ru.